Factors Related to Infection in Systemic Lupus Erythematosus Patients Admitted to the Hospital - Arie Taufik; Rachmat Gunadi Wachjudi; Laniyati Hamijoyo (Indonesian Journal of Rheumatology, 2022)
Background: One of the causes of the increase in hospitalized SLE patients is infection, and it is an important factor in morbidity and mortality, so it is necessary to conduct a research to identify factors related to infection and the type of infection caused in hospitalized SLE patients. Methods: This study is a retrospective, categorical descriptive study utilizing medical records of SLE patients diagnosed with and treated for infection both on admission and during their stay in Hasan Sadikin General Hospital between January 2016 to June 2018. Results: Seventy- four patients were involved into this study. Female were 70 (94.6%), aged <40 years were 69 (93.2%) patients, and all 74 (100%) were entirely in an active disease condition with a mean Mexican systemic lupus erythematosus disease activity (Mex-SLEDAI) score of 9 ± 5.2. Fifty-three (71.6%) subjects experienced major infections. Mucocutaneous and kidney were the most organs involvement found in SLE patients during infection, 63 (85.1%) and 57 (77.0%) respectively. Sixty-two (83.7%) subjects had received corticosteroids before the onset of infection, while pneumonia was the most common infection found in 33 patients (44.6%). This study also noted 12 (16.2%) patients deceased related to infection with most causes were respiratory failure (66.7%). Conclusion: Age less than 40-year-old, mucocutaneous and kidney involvement and previously on corticosteroids were found higher among in hospitalized SLE patients. Most experienced major infections and pneumonia is the most common type of infection.